Kısa Öyküye Kuramsal Bir Yaklaşım Denemesi - Uçan, Hilmi (Kitabevi, 2002)
Short stories, regarded as one of the many ways of narration, has become the more attracted litteral piece as having metaphorical qualities of life with regards to other literal formes. It is now possible to see one-paged stories as well as stories coprising of at least 100-200 pages. What is aimed in this story is to be able make a new definition of short stories; differences between the classical narratives and narrative qualities of modem ones, and to be able to get in touche with the features of short stories, which appeal to the reders, with a theoritical approche.
A Thehortical Approche to Short Story
Keywords: Short Stories; The Art of Narration; Story; Turkish Literature